Relationship between energy consumption and environmental sustainability in OECD countries: The role of natural resources rents - Ulucak, Recep; Danish; Ozcan, Burcu (Elsevier Sci Ltd, 2020)
This study investigates the impact of disaggregated energy consumption and natural resources on environmental sustainability for the Organization for Economic Co-operation and Development (OECD) countries. To this end, CO2 emissions, ecological footprint and carbon footprint data covering the period 1980-2016 are used as proxies for environmental deterioration. The study applies an advanced panel data estimation tool, augmented mean group (AMG) estimator, for the long-run estimation, that allows dependencies across countries and heterogeneity in the slope parameters. The findings of the study indicate that non-renewable energy has a detrimental effect on the environment, while renewable energy reduces deterioration in the environment in terms of ecological footprint and carbon footprint. Natural resource extraction contributes to increasing CO2 emissions, whereas its role is not statistically significant in ecological footprint and carbon footprint. The study provides empirical evidence revealing the requirement for efficient and sustainable natural resource utilization, together with the increasing rate of renewable energy in the energy mix to achieve a sustainable environment and development.
Keywords: Renewable and non-renewable energy; Natural resources rents; Environmental sustainability; Ecological footprint; Carbon footprint; CO2; OECD countries